Transumbilical single-incision laparoscopic-assisted technique for removal of ileocecal foreign body - Zhu, Renzhong (Wideochir Inne Tech Maloinwazyjne, 2018)
The aim of this paper is to present the case of a 40-year-old man who accidentally ingested a piece of metal. The patient complained of having intermittent right lower quadrant abdominal pain for 2 days. An abdominal X-ray was performed, and a piece of metal was found in the right lower quadrant of the abdomen. There was no gas in the abdominal cavity. Surgical treatment was therefore needed. Single-incision laparoscopic surgery (SILS) was attempted with conventional laparoscopic instruments. The foreign body was identified around the ileocecal region, an enterostomy was made and the foreign body was successfully removed. Subsequently, the incised ileocecal was wall sutured. The time for this surgery was 1 h with little bleeding. The patient made a quick recovery with a good cosmetic outcome. Based on this case, the use of SILS-assisted technique in the removal of an ileocecal foreign body proves to be safe and feasible.